Platyscaphites, a new ammonite from the Lower Campanian (Upper Cretaceous) of the United States Western Interior - Cobban, W; Kennedy, W; Landman, N (1999)
A diminutive genus of scaphite, Platyscaphites gen. nov., probably arose from the Scaphites hippocrepis (DeKay, 1828) stock during early Campanian time in the northern part of the United States Western Interior. Three species, all new, are described; they reveal a trend towards progressive size reduction and recoiling to a planispiral shell morphology, accompanied by a possible reduction in adult size. Platyscaphites groatensis sp. nov., the oldest species, occurs low in the zone of Baculites sp. (smooth), and P. elginensis sp. nov., occurs high in that zone; P. fremontensis sp. nov., is found in the succeeding zone of Baculites sp. (weak flank ribs).